Evaluation of Essential and Toxic Elements in the Blood of 0–14-Year-Old Children in Hunan, China From 2013 to 2019: A Retrospective Analysis - Tan, Shan; Yang, Yang; Chen, Zhiheng; Zhao, Lingling; Yang, Zuocheng; Dai, Hongmei; He, Wei; Jiang, Mei; Yao, Yanhua; Huang, Ke; Li, Liu; Zhu, Pengfei; et al. (Frontiers in Public Health, 2022)
Objective The aim was to investigate the distribution and correlation of Ca, Mg, Zn, Cu, Fe, Pb, and Cd in the blood of children aged 0–14 years in Hunan, China, which may serve to provide a basis for clinical guidance on child health. Study Design A retrospective analysis was carried out. Concentrations of all elements were determined by atomic absorption spectrophotometry. Distributions were analyzed and compared among different age, sex, and year groups by the Kruskal–Wallis test, the chi-square test, and the Fisher's exact test. Spearman's rank correlation coefficient was used to evaluate the association between every pair of elements. Results A total of 46,951 children were involved in this study from 2013 to 2019. The median blood levels of elements were 13.51 μmol/L (Cu), 58.69 μmol/L (Zn), 1.70 mmol/L (Ca), 1.40 mmol/L (Mg), 7.46 mmol/L (Fe), 35.00 μg/L (Pb), and 1.00 μg/L (Cd). Girls had a higher level of Ca and lower levels of Pb and Cd than boys. Cu and Ca showed an upward trend, and Mg and Pb showed a downward trend by year. Zn and Fe increased and Ca decreased significantly with age. The deficiency rates of Fe and Zn decreased significantly by year, while Ca and Cu increased significantly by year. Cd exposure in this area was relatively low. Conclusion Most children had normal levels of the essential elements Ca, Cu, and Mg and the toxic elements Pb and Cd. Severe deficiencies in Zn and Fe were observed in the relatively younger children but improved with age. Persistent efforts in reducing Pb exposure might still be needed.